Chondroid Chordoma: An Uncommon Bone Neoplasm - Anita B. Sajnar1 , Neha Bhatt2 , Obaid Noman3 , Pratibha Dawande4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Chordomas are rare, slowly growing, locally aggressive neoplasms of bone that arise from embryonicremnants of the notochord. Chondroid-chordoma is an uncommon variant of chordoma. These tumorstypically occur in the axial skeleton. Here we report a rare occurrence of chondroid variant of chordomaat sacrococcygeal region in a 60 year old female. Magnetic resonance imaging revealed expansile massinvolvingsacrococcygeal region.Gross and microscopic examination confirmed chondroid chordoma.Laterpatient underwent radiotherapy, doingwell,on a one year follow up. Chondroid chordoma is discussed dueto its predilection for occurrence at sacrococcygealregion and its more favorable prognosis compared withthat of conventional chordoma.